Workshop on Developing Gamification Teaching Materials to Enhance Students' Literacy and Numeracy - Feriyanto, F; Zahara, Soffa; Afkar, Taswirul; Istiqomah, Oktavia; Sholikha, Miftakhus (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2024)
This community development program was conducted at SMPN 1 Gedeg, Mojokerto, East Java, to enhance students' literacy and numeracy skills through the development of gamification-based teaching materials integrated with local wisdom. The project, funded by the Ministry of Education, Research, and Technology, aimed to address gaps in digital learning resources and improve teacher competence in creating engaging and effective teaching tools. The methodology involved three phases: preparation, implementation, and evaluation. In the preparation stage, the needs of the school were identified through coordination with school administrators. The implementation phase included workshops and mentoring sessions, where teachers from both SMPN 1 Gedeg and affiliated schools were trained in developing digital learning materials using gamification techniques. Participants showed a significant increase in their knowledge and skills, as demonstrated by a 74.42% improvement in post-test scores. The evaluation phase revealed the program's effectiveness in improving both teachers’ digital competencies and students’ literacy and numeracy performance. However, challenges such as the technological proficiency of senior teachers were identified, highlighting areas for future improvements. Overall, this initiative successfully promoted innovative teaching practices aligned with the national curriculum.